Love in the dark : philosophy by another name - Enns, Diane (Columbia University Press, 2016)
Intimate love opens us up to suffering, sacrifice, and loss. Is it always worth the risk? Consulting philosophers, writers, and poets who draw insights from material life, Diane Enns shines a light on the limits of erotic love, exploring its paradoxes through personal and philosophical reflections. Situating experience at the center of her inquiry, Enns conducts philosophy "by another name," elaborating the ambiguities and risks of love with visceral clarity. Love in the Dark claims that intimacy must accept risk as long as love does not destroy the self. Erotic love inspires an inexplicable affirmation of another but can erode autonomy and vulnerability. There is a limit to love, and appreciating it requires a rethinking of love's liberal paradigms, which Enns traces back to the hostility toward the body and eros in Christianity and the Western philosophical tradition. Against a legacy of an abstract and sanitized love, Enns recasts erotic attachment as an event linked to conditional circumstances. The value of love lies in its intensity and depth, and its end does not negate love's truth or significance. Writing in a lyrical, genre-defying style, Enns delineates the paradoxes of love in its relations to lust, abuse, suffering, and grief to reach an account faithful to human experience